Comparative Analysis of Effectiveness of Inflation Targeting as a Monetary Policy Framework : A case of the United Kingdom and Canada - Singh, Shivalee; Čermáková, Klára; Mach, Petr, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
The main objective of this thesis is to properly analyse the effectiveness of inflation targeting as a monetary policy framework of the United Kingdom and Canada and compare the two countries in this context by looking at its’ effect on the macroeconomic variables of the two countries and giving a comparative analysis of the performance of their respective central banks. As an Economics student, who aspires to achieve a career in Monetary Policy, this thesis would be a great foundation of researching deeply the effectiveness of one of the most important Monetary Policies in the theory of Macroeconomics.
Vedoucí práce: Klára Čermáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses